Small cell neuroendocrine carcinoma of the breast - case series of a common tumour at a rare location - Dilip Harindran Vallathol; Thomas Babu; P S Sreedharan; Sajna VM Kutty; NTK Thanseer; Narayanankutty Warrier (Brazilian Journal of Oncology)
Small cell neuroendocrine carcinoma of the breast is an uncommon primary tumor of the breast with literature limited to case reports and case series. We hereby report 3 cases of small cell neuroendocrine carcinoma of the breast who presented to our institute. One was an elderly lady and the other two were young females. Two of them were of luminal subtype whereas the third was of basal type. One of them occurred in a recurrent setting. The histopathology and immunohistochemistry of all tumors were consistent with neuroendocrine origin. All of them were treated with a combination of chemotherapy, surgery, and radiotherapy. It is important for prognostication as most of them present with a higher grade and stage. Treatment protocols need to be standardized for this rare and aggressive breast tumor.